Bootstrapping systems cointegration tests with a prior adjustment for deterministic terms - Carsten Trenkler (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
In this paper we analyse bootstrap procedures for systems cointegration tests with a prior adjustment for deterministic terms suggested by Saikkonen & Lütkepohl (2000b) and Saikkonen, Lütkepohl & Trenkler (2006). The asymptotic properties of the bootstrap test procedures are derived and their small sample properties are studied. The simulation study also considers the standard asymptotic test versions and the Johansen cointegration test for comparison.
Keywords: C12; C13; C15; C32; 330; Bootstrap; Systems cointegration tests; VEC models